2019
DOI: 10.1787/8c26fee5-en
|View full text |Cite
|
Sign up to set email alerts
|

The lives of teachers in diverse classrooms

Abstract: This document, as well as any data and map included herein, are without prejudice to the status of or sovereignty over any territory, to the delimitation of international frontiers and boundaries and to the name of any territory, city or area. 2 │ EDU/WKP(2019)6 THE LIVES OF TEACHERS IN DIVERSE CLASSROOMS Unclassified OECD EDUCATION WORKING PAPERS SERIES OECD Working Papers should not be reported as representing the official views of the OECD or of its member countries. The opinions expressed and arguments emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Feron and Kankaraš (2019 [181]) found that students were more optimistic, confident, socially engaged and trusting if they reported a sense of belonging to their school. Students who stated that they were bullied at school reported lower levels of optimism, cooperation and emotional control along with higher levels of stress.…”
Section: Gaining and Using Sesmentioning
confidence: 99%
“…Feron and Kankaraš (2019 [181]) found that students were more optimistic, confident, socially engaged and trusting if they reported a sense of belonging to their school. Students who stated that they were bullied at school reported lower levels of optimism, cooperation and emotional control along with higher levels of stress.…”
Section: Gaining and Using Sesmentioning
confidence: 99%
“…There are still considerable challenges when it comes to the design and implementation of educational policy for inclusion, starting with the conceptualisation of inclusive education itself. At the OECD, inclusive education has traditionally been understood as an aspect of equity (the other being fairness) that implies a minimum standard of education for all and, more generally, that people are provided with the minimum skills to participate in society (OECD, 2004 [23]; Field, Kuczera and Pont, 2007 [24]; OECD, 2012 [11]). The project aims to go beyond the definition of inclusive education as a simple dimension of educational equity, though both concepts cannot be thought of separately.…”
Section: Figure 22 the Four Models Of Educationmentioning
confidence: 99%
“…The first phase of the project developed a comprehensive set of reports (OECD, 2018 [7]; OECD, 2018 [30]; OECD, 2019 [31]) and working papers (Cerna et al, 2019[32]; Guthrie et al, 2019[33]; Borgonovi and Pokropek, 2017 [34]; 2018 [35]; Cerna, 2019 [36]; Forghani-Arani, Cerna and Bannon, 2019 [37]; Bilgili, 2017 [38]; 2019 [39]) examining migration-induced diversity and the effects it has on education systems. Following the framework developed in the first phase of the project, the second phase considers broad migration experiences individuals may have, whether direct (foreign-born individuals who migrated) or not (individuals who have at least a parent or guardian who migrated).…”
Section: Migration-induced Diversitymentioning
confidence: 99%
“…Back in 2008, the European Commission launched the European Year of Intercultural Dialogue (European Commission 2007) 'to foster peaceful coexistence, social cohesion and tolerance among European citizens'. Furthermore, the OECD launched a working paper 'The Lives of Teachers in Diverse Classrooms' (Forghani-Arani et al 2019), which acknowledges the challenges teachers face daily. This paper underlines the importance of the teachers' competences, and draws attention to the understanding of diversity, and the indispensable overarching competence 'to practice diversity', such as reflectivity, multi-perspectivity, and the didactical-pedagogical approach to the topic.…”
Section: Theoretical Frameworkmentioning
confidence: 99%